GAYA KEPEMIMPINAN, PEMAHAMAN GOOD GOVERNANCE, LOCUS OF CONTROL, STRUKTUR AUDIT DAN KOMITMEN ORGANISASI - Arya Adi Putra, Kadek; Ariyanto, Dodik (E-Jurnal Akuntansi, 2016)
The needs of the company will be auditing company event shows the importance of the role of auditors in the world economy. Internal auditor's duty refers to a series of internal checking tasks to ensure compliance with procedures and regulations. The purpose of this study was to analyze the influence of leadership style, understanding of good governance, locus of control, audit structure and organizational commitment to the performance of the internal auditors at. SIMAS MSIG Insurance Bali Province. This research was conducted in all branches of PT. SIMAS MSIG Insurance Bali Province eight branch offices located in Bali region in 2015 with the auditor makes a total of 39 people as a sample with saturated sample method. Through multiple linear regression analysis known that the style of leadership, understanding of good governance, locus of control, audit structures positive effect on the performance of the internal auditor at PT. SIMAS MSIG Insurance Bali Province. While variable organizational commitment does not affect the performance of the internal auditor at PT. SIMAS MSIG Insurance Bali Province.
Keywords: Leadership Styl; Understanding Good governance; Locus of Control; Audit Structure; Organizational Commitment; Performance Auditor